Oxidative stress in opium users after using lead-adulterated opium: The role of genetic polymorphism. (October 2018) - Shojaeepour, Saeedeh; Fazeli, Mehdi; Oghabian, Zohreh; Pourgholi, Leyla; Mandegary, Ali
Abstract: Use of lead-adulterated opium has become one of the major sources of lead poisoning in Iran. This study was designed to assess clinical effects and oxidative stress and its association with GSTM1, GSTT1, NQO1, and ALAD genes polymorphisms and blood lead level (BLL) in lead-adulterated opium users. The oxidative stress status in 192 opium users with lead poisoning symptoms measured and compared with 102 healthy individuals. Gluthatione S-transferase (GST)-M1 and -T1 genes deletion, NQO1 rs1800566, and δ-aminolevulinic acid dehydratase (ALAD) rs1800435 polymorphisms were determined using PCR and PCR-RFLP. The relation between the polymorphisms, BLL, and oxidative stress parameters were analysed using multivariate linear regressions. The common symptoms of lead toxicity were gastrointestinal and neurologic complications. Oxidative stress was significantly higher in opium addicts and lipid peroxidation significantly correlated with BLL. There was significant association between ALAD rs1800435 and BLL, and the BLL was significantly lower in the patients with ALAD 1-2 genotype. Use of lead-adulterated opium causes high frequency of lead toxicity symptoms, hematological and biochemical abnormalities, and oxidative stress which are associated with BLL. Route of opioid use and the polymorphism of rs1800435 in ALAD gene are the major determinants of BLL in lead-adulterated opium users. Highlights: Use of lead-adulterated opium is an emerging source of lead poisoning in Iran. Use of lead-adulterated opium causes hematological and biochemical abnormalities and oxidative stress. Blood lead level is associated with toxicities in lead-adulterated opium users. Blood lead level is higher in orally lead-adulterated opium users. Genetic polymorphism of rs1800435 in ALAD gene can determine inter-individual difference in blood lead level.